From clay tablets to AJAX replicating writing and documents in Internet transactions - Mik, Eliza (Journal of Internet Law, 2012)
This article addresses the absence of paper and the challenges of transposing the traditional legal concepts of "writing" and "document" into an environment consisting of interactive and interconnected files. Both "writing" and "documents" are concepts that rely on tangible carriers, such as paper. Accordingly, legal principles involving either concept presume not only a certain durability, but also the stability and confinement of the information conveyed. The mainstream approaches to the concepts of "writing" and "document" are best tested when confronted with Asynchronous JavaScript and XML (AJAX), a suite of technologies enabling Web pages to partially refresh the displayed content in real time. The existing e-commerce laws were drafted in the infancy of the World Wide Web. The Web consisted of static hypertext markup language files, and email was the technology du jour. "Writing" and "documents" are generally discussed in the context of formalities. All e-commerce laws focus on removing obstacles to electronic contracting by enabling electronic messages to meet formal requirements.